1960
DOI: 10.1136/bmj.1.5171.462
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Forced Expiratory Volumes Throughout the Day

Abstract: ESTIMATING ARTERIAL AND MIXED VENOUS pCO, MED] a plateau. Less commonly we have also seen apparent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
2

Year Published

1964
1964
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 1 publication
4
41
0
2
Order By: Relevance
“…Circadian variations in lung function have also been described in patients with stable COPD, but have received considerably less attention [5][6][7][8]. COPD symptoms such as breathlessness are typically described as ''characteristically persistent and progressive'' [1].…”
mentioning
confidence: 99%
“…Circadian variations in lung function have also been described in patients with stable COPD, but have received considerably less attention [5][6][7][8]. COPD symptoms such as breathlessness are typically described as ''characteristically persistent and progressive'' [1].…”
mentioning
confidence: 99%
“…It is difficult to evaluate that study because all of the results were presented as figures. (19) The patients included in that study formed a heterogeneous group with chronic bronchitis or emphysema (with or without asthma), and, during the study period, none of the patients were under pharmacological treatment, which precludes the comparison between our results and those of that study. McCarley et al (20) studied airway patency (as measured by PEF) in COPD patients, using cosinor analysis and describing the circadian rhythm of PEF on 8 consecutive days (at 11:00 a.m., 3:00 p.m., and 7:00 p.m.).…”
Section: Resultsmentioning
confidence: 60%
“…The authors measured FEV 1 and PEF significant differences between diurnal and nocturnal values having been observed in the latter. In another study, one group of authors (19) investigated the magnitude of variations in FVC and FEV 1 between 10 p.m. and 6:00 a.m. in 5 healthy male subjects and 16 male patients with obstructive airway disease, which was severe in 12. The authors found that FVC and FEV 1 were lowest at 6:00 a.m. in both groups, having reported that relatively large spontaneous variations in FVC and FEV 1 occurred between 9:00 a.m. and 5:00 p.m.…”
Section: Resultsmentioning
confidence: 99%
“…The maximal effect of bambuterol occurs during the night, which is shown in this study to be around 4 a.m., i.e. the time when patients often experience a worsening of their symptoms [14][15][16]. In another study, in which bambuterol was given either in the morning or in the evening, the evening administration was found to produce a maximal effect around 4 a.m. about 29% better than placebo [17].…”
Section: Discussionmentioning
confidence: 99%